Complications of Nd:YAG Laser Capsulotomy Following Cataract Surgery - Zehra, Tataheer; Bukhari, Sadia; Muhammad Bilal (Indus Journal of Bioscience Research, 2025)
Background: Posterior capsule opacification (PCO) is the most common delayed complication following cataract surgery. Nd:YAG laser capsulotomy is the standard treatment for PCO; however, it is associated with various complications that may affect visual outcomes. Objective: To evaluate the frequency and pattern of complications following Nd:YAG laser capsulotomy and to identify associated risk factors. Methodology: This hospital-based analytical cross-sectional study was conducted at Al Ibrahim eye hospital from May 2024 to November 2024, including 196 patients who underwent Nd:YAG laser capsulotomy after cataract surgery.  Results: The mean age of patients was 58.6 ± 9.8 years. Complications were observed in 31.6% of patients. The most common complication was raised intraocular pressure (17.3%), followed by intraocular lens pitting (11.2%) and anterior uveitis (9.2%). Cystoid macular edema and retinal detachment occurred in 5.1% and 2.0% of patients, respectively. Patients with complications were older (61.2 ± 8.7 vs 57.4 ± 10.2 years, p = 0.01) and had a longer duration since surgery (20.1 ± 5.8 vs 17.6 ± 6.3 months, p = 0.02). Higher laser energy (72.4 ± 16.8 vs 58.0 ± 17.2 mJ, p